Navigating the Landscape of CBRN-Contaminated Forensic Processes - Labaška, Miroslav; Gál, Miroslav; Nemčeková, Katarína; Svitková, Veronika; Krivjanska, Anna; Ryba, Jozef; Híveš, Ján; Mackuľak, Tomáš (Forensic chemistry, 2024)
[Display omitted] •Complexities in handling forensic evidence contaminated by CBRN materials.•Impact of CBRN agents on fingerprint and DNA recovery and enhancement.•Analysis of physical and chemical decontamination techniques for CBRN risks.•Evaluating decontamination methods and their impact on evidence integrity.•Developing robust forensic strategies for unique CBRN event challenges. The intentional release of Chemical, Biological, Radiological, and Nuclear (CBRN) material in conflict situations, terrorist attacks, or criminal acts poses a significant challenge to forensic investigations. The examination of CBRN incidents necessitates specialised methodologies due to the potential contamination of forensic evidence with CBRN materials. Focusing on forensic evidence, this paper reviews studies investigating the impact of chemical agents, biological materials, and ionising radiation on their recovery and enhancement. It provides an overview of forensic challenges in CBRN incidents, emphasising the intricate relationship between evidence recovery, decontamination strategies, and the preservation of forensic integrity. As CBRN incidents continue to pose threats, advancements in forensic science are imperative for effective investigations and the pursuit of justice. This paper explores the complexities surrounding incidents involving CBRN material, emphasizing the crucial role of forensic science in elucidating the modus operandi for effective event management and reconstruction. It is intended to offer the community of interest a concise overview of the potential difficulties and risks associated with handling CBRN-contaminated evidence, while also bringing attention to potential solutions.